Association between the Anatomy of the Mandibular Canal and Facial Types: A Cone-Beam Computed Tomography Analysis. (10th September 2018) - dos Santos Oliveira, Rudyard; Maria Gomes Oliveira, Arlete; Cintra Junqueira, José Luiz; Kühl Panzarella, Francine
Abstract : We evaluated the anatomical variations of the mandibular canal associated with various facial types, age, sex, and side of the face studied. We analyzed 348 hemimandibles in subjects without a history of trauma, lesions in the lower arch, or orthognathic or repair surgery in the posterior mandible. Facial type was determined using the VERT index. The canal path was classified as Type 1 (a large, single structure passing very close to the root tips); Type 2 (a canal passing closest to the mandibular base); and Type 3 (a canal present in the posterior mandibular region, with a lower canal running through the mandibular branch, reaching the anterior region). Bifid canals (type 3) were classified into four categories according to the course and number of mandibular canals. The brachyfacial and mesofacial types presented a Type 1 canal in 95.5% (n = 166 ) of subjects, in dolichofacial types, 68.2% (n = 45 ) presented a Type 2 canal, while in the mesofacial type, a lower prevalence of the bifid mandibular canal was observed (13.0%, n = 23 ) than in the other facial types. The bifid canal showed significant association with facial type only (p < 0.05 ), but no significant association was observed with the anterior loop type (p > 0.05 ). Facial type is significantly associated with the path and morphological variations of the mandibular canal, independently of the side of the face studied, age, and sex.